2015
DOI: 10.1007/s00467-015-3113-7
|View full text |Cite
|
Sign up to set email alerts
|

Severe neutropenia in children after renal transplantation: incidence, course, and treatment with granulocyte colony-stimulating factor

Abstract: Decreasing immunosuppressive or antimicrobial medications carries the risk of acute rejection or infection. Off-label treatment with G-CSF may present a safe and effective alternative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
2
20
4
Order By: Relevance
“…Although G-CSF dosing in our study was variable, the average G-CSF dose administered was similar to the dose recommended in the oncology population (5 mcg/kg/day) 22 and administered in other trials of kidney transplant patients with leukopenia. 6,9,15,16 Following administration of mean 2.1 ± 1.9 doses of G-CSF, we observed WBC count recovery in median 9 (IQR 4-14) days, which is longer than previously reported in the literature. 5,6,15,16 Rather than a lack of efficacy in our cohort, this discrepancy likely reflects the reduced laboratory monitoring frequency for our patients managed in the outpatient setting.…”
Section: Discussioncontrasting
confidence: 41%
See 3 more Smart Citations
“…Although G-CSF dosing in our study was variable, the average G-CSF dose administered was similar to the dose recommended in the oncology population (5 mcg/kg/day) 22 and administered in other trials of kidney transplant patients with leukopenia. 6,9,15,16 Following administration of mean 2.1 ± 1.9 doses of G-CSF, we observed WBC count recovery in median 9 (IQR 4-14) days, which is longer than previously reported in the literature. 5,6,15,16 Rather than a lack of efficacy in our cohort, this discrepancy likely reflects the reduced laboratory monitoring frequency for our patients managed in the outpatient setting.…”
Section: Discussioncontrasting
confidence: 41%
“…6,9,15,16 Following administration of mean 2.1 ± 1.9 doses of G-CSF, we observed WBC count recovery in median 9 (IQR 4-14) days, which is longer than previously reported in the literature. 5,6,15,16 Rather than a lack of efficacy in our cohort, this discrepancy likely reflects the reduced laboratory monitoring frequency for our patients managed in the outpatient setting. Furthermore, we defined study inclusion based on leukopenia (WBC < 3000 cells/μL), 1,3,6,16 but all patients with available ANC data were neutropenic (ANC < 1000 cells/μL) at the time of G-CSF initiation.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Leukopaenia was a very common finding in this study and its development was significantly associated with the higher MMF dose. Previous studies have reported leukopaenia rates of 18-36% by 12 months with differences between studies likely to relate to factors such as the use of concomitant medications such as trimethoprim/sulphamethoxazole and antiviral prophylaxis [8][9][10][19][20][21]27,28 . The peak onset of leukopaenia was at 3 months post-transplant, coinciding with protocolised prednisolone reduction and hence a reduced drive to neutrophil margination.…”
Section: Discussionmentioning
confidence: 99%